A chronology of depositional coastal landforms of the Baltic Sea: Luminescence dating of sandy sediments and patterns of human settlement at the ancient Ventspils Lagoon. (5th December 2022) - Kalińska, Edyta; Breijers, Edijs; Alexanderson, Helena; Krievāns, Māris; Bērziņš, Valdis
Abstract: The ancient Ventspils Lagoon is an area where human settlements have been located on former coastal landforms and sediments. However, the chronology of its development has so far not been studied in detail. Since the ancient lagoon is dominated by sand deposition, optically stimulated luminescence dating (OSL) was used to determine when the ancient coast was formed. Twenty-one OSL samples gave a wide age range, between 8.57 ± 0.65 ka and 73.8 ± 8.3 ka. Twelve of the ages fall in the Late Glacial and Holocene and document the development of the lagoon between the Baltic Ice Lake stage (∼16 ka) and the Littorina Sea stage (∼8 ka). The new dates correspond to some extent with previously modelled shorelines for the Ventspils Lagoon and to radiocarbon ages from archaeological sites in the area. One date, 16.0 ± 1.3 ka, falls in the period before the Baltic Ice Lake and represents either a very early Baltic Ice Lake stage or, less likely, the Venta glacial lake prior to the Baltic Ice Lake. One date, 5.09 ± 0.42, is likely underestimated. Seven samples yielded dates between 21.5 ± 1.5 ka and 73.8 ± 8.3 ka, which corresponds to the Early and Middle Weichselian in the Baltic region. The samples in this latter group are likely overestimating the true age due to insufficient exposure to sunlight during deposition. Highlights: Depositional time frame of the ancient Ventspils Lagoon. Part of OSL datings fall in interval between the Baltic Ice Lake stage and post-maximum Litorina Sea stage. Partial correspondence of OSL and radiocarbon datings with the previously modelled shorelines for the Ventspils Lagoon. Coastal sediment deposition took place between 12.6 ± 2.8 ka and 5.09 ± 0.42 ka. Older dates suffer from incomplete bleaching because of the skewness of dose distributions and large overdispersion.